Nursing of a breast cancer patient with skin ulcer treated by Traditional Chinese Medicine encircling application (中药围敷疗法治疗乳腺癌性溃疡1例的护理体会) - LIANG Chen (梁晨); LIU Shuhong (刘书红); YAN Kang (严康); ZHAO Yanan (赵亚楠) (中西医结合护理)
To explore the effect of Traditional Chinese Medicine encircling application therapy in the treatment of skin ulcer in a breast cancer patient. In addition to routine nursing interventions such as daily support, nutrition guidance and emotional care, the Traditional Chinese Medicine encircling application based on syndrome differentiation was carried out relieve the symptons of ulcer and improve the wound healing and patient’s quality of life. (本文总结中药围敷疗法治疗1例乳腺癌性溃疡患者的护理经验。在生活管理、饮食指导、情志护理等整体护理基础上, 基于辨证分型, 采取中药围敷疗法治疗癌性溃疡, 通过肿瘤绿色调护技术改善患者溃疡症状, 促进创面愈合, 提高肿瘤患者生活质量。)